Ancient Wine : The Search for the Origins of Viniculture - McGovern, Patrick E. (Book collections on Project MUSE., 2019)
"A richly illustrated account of the story of ancient viniculture. In a new afterword, the author discusses exciting recent developments in the understanding of ancient wine, including a new theory of how viniculture came to central and northern Europe"--